THE USE OF ROLE PLAY TECHNIQUE TO IMPROVE STUDENTS’ ENGLISH ORAL COMMUNICATION - Mutiatun Nasihah (Journal of English for Academic and Specific Purposes, 2019)
This study aims at describing the implementation of role play technique in order to improve students’ English oral communication. The subjects of this study were forty students of UIN Maulana Malik Ibrahim Malang majoring at Islamic Banking who are taking English 1 as a compulsory subject at semester III. To meet the objective of this study, Classroom Action Research (CAR) which involved planning, acting, observing, and reflecting was used as the design of research. The data of this qualitative study were gathered through observation, interview, and documentation. Meanwhile, the result of this study was presented descriptively based on the phenomena occurred during the implementation of role-play in the process of teaching and learning. In addition, the findings of this study revealed that by applying role-play technique, the students are able to improve their English oral communication as well as increase their motivation in learning English. Role play technique allows the students to be more active in the class as they get much opportunity to speak based on the context given in a real-life situation..